Serotipe Virus Dengue di Tiga Kabupaten/Kota Dengan Tingkat Endemisitas DBD Berbeda di Propinsi Jawa Barat - Heni Prasetyowati; Endang Puji Astuti (ASPIRATOR - Journal of Vector-borne Disease Studies, 2010)
The incidence rate of Dengue Hemorrhagic Fever (DHF) disease in Indonesia is increasing over years. DHF outbreaks happen in many provinces of Indonesia. West Java is a DHF endemic province. Nearly all districts/municipalities at the West Java Province are endemic areas and have reported DHF outbreaks. Factors supporting high incidence rate of DHF are tropical climate of Indonesia and the circulation of four dengue virus serotypes. The study aimed to identify dengue virus serotype distribution in the districts with different DHF endemic at the Province of Jawa Barat. The study was observational with cross sectional design. Samples consisted of 60 samples of blood serum of patients serologically infected by dengue virus. Samples came from three districts/municipalities with different DHF endemic. Dengue virus serotype of samples was detected using nested RT-PCR (Reserve Transcription Polymerase Chain Reaction) examination.Results showed that, four serotypes of dengue virus could be isolated from serum samples. Out of all positive samples, Den-2 was the serotype most frequently appeared (55%) followed by Den-3 (29%), Den-1 (9.6%) and Den-4 (6.4%). At dengue high endemic areas there were 4 serotypes of dengue virus Den-3 (6 times), Den-2(twice), Den-4 and Den-1 (once each). At medium endemic areas there were 4 serotypes of dengue virus, i.e. Den-2 (9 times), Den-3 (twice), Den-1 and Den-4 (once each). At low endemic areas there were two serotypes, i.e. Den-2 (6 times) and Den-1 (once).